Historical Dictionary of Contemporary Art. - Morgan, Ann Lee (Historical dictionaries of literature and the arts., 2016)
The Historical Dictionary of Contemporary Art details the history of contemporary art through a chronology, an introduction, and an extensive bibliography. The dictionary section has over 900 cross-referenced entries on important artists, styles, terms, and movements.